Validation de la version francophone d’une échelle composite multidimensionnelle pour l’évaluation de la douleur postopératoire chez les chats - Steagall, Paulo V.M. (Can Vet J, 2017)
Validation of the French version of the UNESP-Botucatu multidimensional composite pain scale for assessing postoperative pain in cats. The aim of this study was to validate the French version of the UNESP-Botucatu multidimensional composite pain scale (MCPS-Fr) to assess postoperative pain in cats. Two veterinarians and one DVM student identified three domains of behavior based on video analyses: “psychomotor change”, “protection of the painful area” and “physiological variables”. Internal consistency was excellent (Cronbach’s alpha coefficient of 0.94, 0.90 and 0.61, respectively). Criterion validity was good to very good when evaluations from the three observers were compared with a “gold standard”. Inter- and intra-rater reliability for each scale item were good to very good. The optimal cut-off point identified with a ROC curve was > 7 (scale range 0–30 points), with a sensitivity of 97.8% and specificity of 99.1%. The MCPS-Fr is a valid, reliable and responsive instrument for assessing acute pain in cats undergoing ovariohysterectomy. (Translated by Dr. Beatriz Monteiro)